2014
DOI: 10.1002/ejlt.201300323
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical fluid extraction of wheat bran oil: Study of extraction yield and oil quality

Abstract: The supercritical fluid extraction (SFE) of wheat bran oil with pure supercritical carbon dioxide at different extraction pressure (25, 40 and 55 MPa) and temperature (40, 70 and 95 ºC) has been studied. Since wheat bran is characterized by having an important content of bioactive compounds such as alkylresorcinols (AR) and other phenolic compounds, the content of such compounds in the extracted oil was evaluated in order to establish oil quality. The influence of extraction pressure and temperature and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
4
13
0
Order By: Relevance
“…To better understand the effects of by-product storage on the quality of the extracted oil, total FA composition was determined. In agreement with the literature, [11,12] PUFA were the main FA class, being mainly constituted by linoleic acid (LA, C18:2 n-6) which represented more than 50% of total FA. As reported in Table 3, the FA composition significantly changed among the analyzed by-products.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To better understand the effects of by-product storage on the quality of the extracted oil, total FA composition was determined. In agreement with the literature, [11,12] PUFA were the main FA class, being mainly constituted by linoleic acid (LA, C18:2 n-6) which represented more than 50% of total FA. As reported in Table 3, the FA composition significantly changed among the analyzed by-products.…”
Section: Discussionsupporting
confidence: 90%
“…Durante et al [10] reported that durum wheat bran oil is a rich source of vitamin E forms, carotenoids, quinones, triacylglycerols (TAG), diacyglycerols (DAG), and free fatty acids (FFA). Rebolleda et al [11] and Suresh Kumar and Gopala Krishna [12] also reported a noticeable presence of alkylresorcinols and steryl ferulates in wheat bran oil extracted with diverse technologies (solvent and/or CO 2 supercritical fluid extraction). Since the by-products from durum wheat bran could represent a potential source of added-value edible oil and/or other products for diverse non-food industrial sectors, the aim of the present study was to extract and characterize the lipid and phenolic fractions obtained from different durum wheat bran by-products deriving from diverse debranning and milling steps and subjected to storage with the final purpose of further valorizing the durum wheat bran and thus improving the sustainability of the wheat chain.…”
Section: Introductionmentioning
confidence: 99%
“…Radical scavenging capacity of the tea seed oils against ABTS•+ was measured as described by Rebolleda et al . Briefly, ABTS•+ was freshly prepared by mixing 14 mM ABTS with an equal volume of 4.95 mM potassium persulfate and kept for 16 h in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of oils from cottonseed flakes, rapeseed cake, and wheat bran using SCF‐CO 2 method has been reported previously . However, no information is available in the extraction of oils from tea seed cake, which is still rich in oils .…”
Section: Introductionmentioning
confidence: 99%
“…The five BTBOs, quenching ABTS ·+ with a narrow TE range of 5.03-6.94 μmol TE/g oil, were proven to be of better quality when compared to the recommended minimum TEAC value (2.2 μmol TE/g) [31]. The capacity of scavenging ABTS ·+ of BTBO is comparable to that of soybean oil (6.21-7.10 μmol/g), but is higher than that of corn oil (3.03-4.51 μmol/g) and sunflower oil (3.11-4.34 μmol/g) [12], and lower than wheat bran oil (0.23-0.41 mmol/g) as extracted by supercritical fluids [24].…”
Section: Antioxidant Propertiesmentioning
confidence: 81%